Religious Transformation in Maya Guatemala : Cultural Collapse and Christian Pentecostal Revitalization - Hawkins, John P. (Book collections on Project MUSE., 2021)
Drawing on over fifty years of research and data collected by field-school students, Hawkins argues that two factors--cultural collapse and systematic social and economic exclusion--explain the recent religious transformation of Maya Guatemala and the style and emotional intensity through which that transformation is expressed.